Search for tt[bar] resonances in fully hadronic final states in pp collisions at √s = 13 TeV with the ATLAS detector - Aad, Georges; Andrei, George Victor; Bartels, Falk; Bolz, Arthur; Czurylo, Marta; Dittmeier, Sebastian; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Helary, Louis; Jongmanns, Jan; Klassen, Martin; et al. (Journal of high energy physics, 2020)
This paper presents a search for new heavy particles decaying into a pair of top quarks using 139 fb−1 of proton-proton collision data recorded at a centre-of-mass energy of √s = 13 TeV with the ATLAS detector at the Large Hadron Collider. The search is performed using events consistent with pair production of high-transverse-momentum top quarks and their subsequent decays into the fully hadronic final states. The analysis is optimized for resonances decaying into a tt¯ pair with mass above 1.4 TeV, exploiting a dedicated multivariate technique with jet substructure to identify hadronically decaying top quarks using large-radius jets and evaluating the background expectation from data. No significant deviation from the background prediction is observed. Limits are set on the production cross-section times branching fraction for the new Z′ boson in a topcolor-assisted-technicolor model. The Z′ boson masses below 3.9 and 4.7 TeV are excluded at 95% confidence level for the decay widths of 1% and 3%, respectively.
The Atlas collaboration: G. Aad, V. Andrei, F. Bartels, A.E. Bolz, M. Czurylo, S. Dittmeier, M. Dunford, D.E. Ferreira de Lima, S. Franchino, L. Helary, J. Jongmanns, M. Klassen, A. Krishnan, M. Mkrtchyan, F. Napolitano, P. Ott, A. Schoening, H.-C. Schultz-Coulon, T. Spieker, R. Stamen, P. Starovoitov, S. Suchek, L. Vigani, S. Weber, M. Wessels, X. Yue [und 2922 weitere]
Gesehen am 21.01.2021
Im Titel steht der zweite Buchstabe t mit einem Oberstrich
Im Titel steht der Buchstabe s unter dem Wurzelzeichen